Unlocking T cell exhaustion: Insights and implications for CAR-T cell therapy - Dian Xiong; Haijun Yu; Zhi-Jun Sun (Elsevier, 2024)
Chimeric antigen receptor T (CAR-T) cell therapy as a form of adoptive cell therapy (ACT) has shown significant promise in cancer treatment, demonstrated by the FDA-approved CAR-T cell therapies targeting CD19 or B cell maturation antigen (BCMA) for hematological malignancies, albeit with moderate outcomes in solid tumors. However, despite these advancements, the efficacy of CAR-T therapy is often compromised by T cell exhaustion, a phenomenon that impedes the persistence and effector function of CAR-T cells, leading to a relapse rate of up to 75% in patients treated with CD19 or CD22 CAR-T cells for hematological malignancies. Strategies to overcome CAR-T exhaustion employ state-of-the-art genomic engineering tools and single-cell sequencing technologies. In this review, we provide a comprehensive understanding of the latest mechanistic insights into T cell exhaustion and their implications for the current efforts to optimize CAR-T cell therapy. These insights, combined with lessons learned from benchmarking CAR-T based products in recent clinical trials, aim to address the challenges posed by T cell exhaustion, potentially setting the stage for the development of tailored next-generation approaches to cancer treatment.